SP4.1.7 Colorectal Cancer: Pathway Disruptions as a Result of COVID-19. (28th October 2021) - Spyropoulou, Liana E; Curley, Daniel; Li, Mimi; Martin, Estelle; Wynn, Greg; Doulias, Triantafyllos
Abstract: Aims: COVID-19 has impacted diagnosis and treatment of colorectal cancer. Efforts to minimise patient contact have caused delays in cancer pathways, generating a potential risk to patient care. We aim to identify the pandemic effect on colorectal referral pathways. Methods: All cancer referrals during March-June 2020 were reviewed to obtain information on the timeline and planning of investigation and treatment. The data was compared to evidence from the same referral period in 2019. Results: 681 referrals were received during March-June 2020, compared to 1032 in 2019, indicating a 34% decrease. The majority of patients were reviewed in telephone clinic (76.2%) rather than physical appointments (15.4%). Although the commonest mode of investigation was endoscopy(46.2%), there was increased use of CT scan(35.8%). 114(17.1%) patients were not investigated, of which 40(35.1%) declined investigation, primarily due to COVID-19 apprehension. 6 patients were re-referred and 67(58.8%) were removed from the pathway for unknown reasons. 1 patient was subsequently admitted as an emergency. There were 44 new diagnoses of colorectal cancer based on MDT discussion, of which 14(31.8%) breached the investigation and 20(45.5%) the treatment date. 18 underwent curative surgery compared to 47 in the same period in 2019, indicating 61.7% less operative activity. Conclusions: COVID-19 has changed surgical practice, forcing alternative clinic, investigation and treatment methods. Disruption of colorectal pathways is causing reduced referrals, investigation delays and less surgical activity. Delayed presentation with advanced disease may deprive the opportunity of treatment with curative intent.